Loss of Gsα Early in the Osteoblast Lineage Favors Adipogenic Differentiation of Mesenchymal Progenitors and Committed Osteoblast Precursors. (November 2014) - Sinha, Partha; Aarnisalo, Piia; Chubb, Rhiannon; Ono, Noriaki; Fulzele, Keertik; Selig, Martin; Saeed, Hamid; Chen, Min; Weinstein, Lee S; Pajevic, Paola Divieti; Kronenberg, Henry M; Wu, Joy Y
ABSTRACT In humans, aging and glucocorticoid treatment are associated with reduced bone mass and increased marrow adiposity, suggesting that the differentiation of osteoblasts and adipocytes may be coordinately regulated. Within the bone marrow, both osteoblasts and adipocytes are derived from mesenchymal progenitor cells, but the mechanisms guiding the commitment of mesenchymal progenitors into osteoblast versus adipocyte lineages are not fully defined. The heterotrimeric G protein subunit Gsα activates protein kinase A signaling downstream of several G protein‐coupled receptors including the parathyroid hormone receptor, and plays a crucial role in regulating bone mass. Here, we show that targeted ablation of Gsα in early osteoblast precursors, but not in differentiated osteocytes, results in a dramatic increase in bone marrow adipocytes. Mutant mice have reduced numbers of mesenchymal progenitors overall, with an increase in the proportion of progenitors committed to the adipocyte lineage. Furthermore, cells committed to the osteoblast lineage retain adipogenic potential both in vitro and in vivo. These findings have clinical implications for developing therapeutic approaches to direct the commitment of mesenchymal progenitors into the osteoblast lineage. © 2014 American Society for Bone and Mineral Research